Teaching-focused academic appointments in Australian universities : recognition, specialisation or stratification. - Probert, Belinda (Office for Learning and Teaching, 2013)
This report uses Department of Industry, Innovation, Science, Research and Tertiary Education (DIISRTE) data on teaching-only appointments in Australian universities to describe their growth, their distribution by institution, and in those universities with significant numbers, their distribution by discipline and level. The report uses a case study approach to identify the range of policies being used to shape the appointment and career opportunities of teaching only staff, and discusses the likely impact on the quality of teaching and learning in different institutions, as well as the status of teaching in the wider academic culture. [Executive summary]